Exercise induced changes in cutaneous and pulmonary water loss in buffaloes - AGGARWALI, ANJULI; UPADHYAY, R C (The Indian Journal of Animal Sciences, 2013)
Skin and pulmonary evaporative losses and the changes induced due to exercise in hot humid conditions were measured in young buffaloes. Water loss from skin and pulmonary system at rest was 492±57-.90 m·2 hrl and 72.43 ±6.18 g m-2 hr-1 respectively. The corresponding increase after 'I hr exercise on treadmill was 54% and 60%. Evaporative losses increase with exercise. The exercise increased ,evaporative losses and loss through the skin remained higher than respiratory water loss.Sweating in buffaloes was mort closely controlled by skin temperuture than by ambient temperature. Tidal volume. dead space ventilation and RQ decreased after exercise and pulmonary ventilation. volume of oxygen consumed and alveolar ventilation increased after 1 hr of exercise.